Daptomycin-Impregnated PMMA Cement against Vancomycin-Resistant Germs: Dosage, Handling, Elution, Mechanical Stability, and Effectiveness - Martina Humez; Eugen Domann; Kai M. Thormann; Christian Fölsch; Rainer Strathausen; Sebastian Vogt; Volker Alt; Klaus-Dieter Kühn (MDPI AG, 2023)
Background: The number of periprosthetic joint infections caused by vancomycin-resistant pathogens is increasing. Currently, no PMMA cement is commercially available to cover VRE. Daptomycin shows promising results in treating infection, offering a good safety profile and a reduced risk of developing resistance. The purpose of this in vitro study was to investigate the mechanical stability, handling properties, elution behavior, and antimicrobial effectiveness of PMMA cement loaded with three different daptomycin concentrations in comparison to commercially available antibiotic-loaded bone cement (ALBC). Methods: Mechanical properties and handling characteristics (ISO 5833, DIN 53435), HPLC elution, antimicrobial effectiveness with proliferation assay (DIN 17025), and inhibition zone testing were investigated. Results: All tested daptomycin concentrations met the ISO and DIN standards for mechanical strength. Loading of 40 g of PMMA cement with 0.5 g of daptomycin did not show any antimicrobial effectiveness, in contrast to 1.0 g and 1.5 g. PMMA cement with 1.5 g of daptomycin was the best in terms of elution and effectiveness, and it showed good ISO mechanical strength; ISO doughing was sticky for a little longer and setting was faster compared to the vancomycin-containing reference cement. Conclusion: PMMA cement containing 0.5 g of gentamicin and 1.5 g of daptomycin could be a good alternative to the already established COPAL® (Wehrheim, Germany) G+V for the treatment of PJIs caused by VRE.